Decision usefulness of net income versus comprehensive income: case of financial firms in Malaysia - Leong Yew, Chong; Abdul Latiff, Ahmed Razman; Ong, Tze San (Univ. of Malaya, 2020)
Manuscript type: Research paper Research aims: This paper aims to examine the decision usefulness of net income (NI) which includes predictive power and value relevance by comparing it with comprehensive income (CI), for financial firms in Malaysia. Design/Methodology/Approach: This study uses panel data analysis techniques which focus on unbalanced panel dataset of 2012 to 2017, obtained from 29 financial firms listed in Malaysia. Research findings: Results show that in the case of predictive power tests, there is insufficient evidence to conclude that one accounting metric has better predictive power than the other. In the case of value relevance, results show that NI is better than CI when using the price and return models. This indicates that NI is more decision useful to investors than CI for financial firms in Malaysia. Theoretical contribution/Originality: This study expands on the literature of decision usefulness of NI (in comparison to CI) for financial firms within an emerging economy, such as Malaysia, which has a smaller and less efficient market. The findings support the agency theory, particularly the Type II agency problem, which show that there is a conflict between controlling and non-controlling shareholders. This outcome may reduce the demand for quality reporting for external shareholders. This study is related to fair value accounting (FVA) which is still underexplored in the Malaysian setting. The outcome may provide some insights into the financial statements used by investors for understanding the effect of FVA on reported earnings in Malaysia. Such evidence is currently lacking. Practitioner/Policy implications: The findings may be helpful to investors in making better investment decisions in the Malaysian market. This study may benefit academicians by expanding the literature on decision usefulness of FVA in an emerging economy. The outcome derived offers a body of knowledge to academia as a reference for future research. This paper may also be relevant to the standard setters, regulators, and policymakers as it offers empirical evidence on the decision usefulness of accounting information disclosures in the context of an emerging country such as Malaysia. Research limitation/Implications: The limitation of this study lies in the small sample size used, thereby reducing the generalisability of the findings. Larger sample size may add robustness to the results.